Studi Perbedaan Fenotipe Kambing Perah Berdasarkan Analisis Canonikal - Muadz Abdurrahman; Afton Atabany; Bagus Priyo Purwanto; Anneke Anggraeni (Syntax Literate, 2023)
Crossbreeding is carried out with the aim of enhancing and combining favorable traits between different breeds. The results of crossbreeding can be analyzed through genetic distance measured by various parameters, including morphometric measurements of livestock bodies. This study aims to analyze the morphometric diversity based on body measurements and canonical analysis in PE, Saanen, and Sapera goats to determine their genetic proximity. The research utilized a quantitative descriptive method using primary and secondary data from the BALITNAK Ciawi dairy goat station through a canonical analysis approach. The study and collection of primary and secondary data were conducted from March to April 2022. The research was carried out at the BALITNAK Dairy Goat Research Station in Ciawi Subdistrict, Bogor Regency. The results of this study indicate that the genetic distance between Sapera and Saanen goats is closer than between Sapera and PE goats. Furthermore, in terms of body measurements, the measurements of Sapera goats are closer to the Saanen goats compared to the PE goats. It can be concluded that the body size of Sapera goats is more similar to that of PE goats, while their external appearance is closer to the Saanen goats, which have predominantly white fur color.